"We Are Considered Undesirable Foreigners" in "This Our Texas": Mexican American Settler Nativism in Caballero. (10th July 2018) - Franks, Travis
Abstract: This essay explores settler nativism as a means of better understanding the politics of belonging and nationhood in Caballero . By specifically focusing on Caballero 's characterization of Santiago, the essay demonstrates how settler nativist belonging is characterized by an anxiety over being dispossessed, both from within and without. As a colonizer descendant, Santiago interprets power derived from property ownership and generations of lived experience within a patriarchal system as justifiable claims to his entitled sense of belonging. These claims are undermined, then, by the peons who abandon his rancho and the Anglo-Americans who threaten to take away his land and family. More broadly, the analysis performed in the essay investigates how the novel's themes of conflict and reconciliation along the US-Mexico borderlands perpetuate the erasure of indigenous presence. Indeed, this rereading of a landmark Mexican American novel demonstrates potential intersections between settler colonial theory and Chicana/o literary studies.